2022
DOI: 10.3390/ijerph19031697
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Healthcare Utilization in Italy: How Important Are Barriers to Access?

Abstract: With the ageing population, equitable access to medical care has proven to be paramount for the effective and efficient management of all diseases. Healthcare access can be hindered by cost barriers for drugs or exams, long waiting lists or difficult access to the place where the needed healthcare service is provided. The aim of this paper is to investigate whether the probability of facing one of these barriers varies among individuals with different socio-economic status and care needs, controlling for geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This data is in line with most studies, which have confirmed that dental infection is the most common cause of neck abscesses [11]. These conditions are typically related to the lack of dental care due to the high costs of dentists, indifference, and poor knowledge about oral health with associated irregular tooth brushing [12].…”
Section: Discussionsupporting
confidence: 88%
“…This data is in line with most studies, which have confirmed that dental infection is the most common cause of neck abscesses [11]. These conditions are typically related to the lack of dental care due to the high costs of dentists, indifference, and poor knowledge about oral health with associated irregular tooth brushing [12].…”
Section: Discussionsupporting
confidence: 88%
“…Healthcare services utilization, including mammogram screening utilization by the public, is influenced by numerous barriers [ 16 , 26 , 27 , 28 ]. Our study revealed that more than one-third of the HCWs working in the MOH were not aware of the MOH, Saudi Arabia’s recommendation for mammogram screening for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the NHS allows universal access to healthcare; the Ministry of Health decides on services to be delivered and national funds are allocated to the regions, which administer and plan healthcare activities by organizing supply. However, due to existing differences in this respect, a general strong north-south gradient for healthcare access and utilization emerges, showing a worsening situation in the latter [ 85 ]. In Italy, three clusters/levels of RHS performance can be identified, [ 86 ]: excellent, including Lombardy, where the health system is reported as one of the best in the country; intermediate, including Marche; and critical, including Calabria.…”
Section: Discussionmentioning
confidence: 99%